(untitled) (Revista de Física Médica, 2020)
Introduction: In the present work, we aimed to present an alternative methodology to the use of commercial devices for daily quality assurance of the linac energy in the clinic using the electronic portal-imaging device combined with a pair of cylindrical aluminum pieces. Methodology: With an external degradation of beam energy, we achieved a modification of around 2% (considered as clinically relevant) in the representative energy parameter (PDD20,10: ratio of dose percentage at 20 and 10 cm depths, respectively). The proposed methodology was then validated for the detection of this beam perturbation. Results: We observed that the methodology was able to distinguish the intentioned deviations performed in photon energy with a good reproducibility, obtaining threshold-warning levels. Conclusions: The new methodology allows to establish a warning in case of a deviation clinically relevant in beam energy quality with the only use of the portal-imaging system together with a couple of aluminium pieces. The system has demonstrated to be reliable as well as easy to implement without needing extra equipment.